Root Endophytes and Ginkgo biloba Are Likely to Share and Compensate Secondary Metabolic Processes, and Potentially Exchange Genetic Information by LTR-RTs - Zou, Kai; Liu, Xueduan; Hu, Qi; Zhang, Du; Fu, Shaodong; Zhang, Shuangfei; Huang, Haonan; Lei, Fangying; Zhang, Guoqing; Miao, Bo; Meng, Delong; Jiang, Luhua; et al. (Frontiers in Plant Science, 2021)
Ginkgo Biloba is a pharmaceutical resource for terpenes and flavonoids. However, few insights discussed endophytes' role in Ginkgo, and whether genetic exchange happens between Ginkgo and endophytes remains unclear. Herein, functional gene profiles and repetitive sequences were analyzed to focus on these issues. A total of 25 endogenetic strains were isolated from the Ginkgo root and distributed in 16 genera of 6 phyla. Significant morphological diversities lead to the diversity in the COG functional classification. KEGG mapping revealed that endophytic bacteria and fungi potentially synthesize chalcone, while endophytic fungi might also promote flavonoid derivatization. Both bacteria and fungi may facilitate the lignin synthesis. Aspergillus sp. Gbtc_1 exhibited the feasibility of regulating alcohols to lignans. Although Ginkgo and the endophytes have not observed the critical levopimaradiene synthase in ginkgolides synthesis, the upstream pathways of terpenoid precursors are likely intact. The MVK genes in Ginkgo may have alternative nonhomologous copies or be compensated by endophytes in long-term symbiosis. Cellulomonas sp. Gbtc_1 became the only bacteria to harbor both MEP and MVA pathways. Endophytes may perform the mutual transformation of IPP and DMAPP in the root. Ginkgo and bacteria may lead to the synthesis and derivatization of the carotenoid pathway. The isoquinoline alkaloid biosynthesis seemed lost in the Ginkgo root community, but L-dopa is more probably converted into dopamine as an essential signal-transduction substance. So, endophytes may participate in the secondary metabolism of the Ginkgo in a shared or complementary manner. Moreover, a few endophytic sequences predicted as Ty3/Gypsy and Ty1/Copia superfamilies exhibited extremely high similarity to those of Ginkgo. CDSs in such endophytic LTR-RT sequences were also highly homologous to one Ginkgo CDS. Therefore, LTR-RTs may be a rare unit flowing between the Ginkgo host and endophytes to exchange genetic information. Collectively, this research effectively expanded the insight on the symbiotic relationship between the Ginkgo host and the endophytes in the root.